Evaluation of the blood–perilymph barrier in ears with endolymphatic hydrops. (2nd August 2021) - Yoshida, Tadao; Kobayashi, Masumi; Sugimoto, Satofumi; Teranishi, Masaaki; Naganawa, Shinji; Sone, Michihiko
Abstract: Background: Otological diseases including Meniere's disease (MD) involve endolymphatic hydrops (EH), which can be visualized by magnetic resonance imaging (MRI) with gadolinium contrast agents, but the temporal changes of contrast in the inner ear have not been evaluated. Objectives: We investigated the permeability of the blood–perilymph barrier (BPB) in ears with EH to evaluate the severity of the inner ear disturbances. Materials and methods: The study included 32 ears from 16 patients with EH or related diseases who underwent MRI. The permeability of the BPB was assessed by the signal–intensity ratio (SIR) at four-time points: before and at 10 min, 4 h, and 24 h after administration of gadolinium for assessing EH. Results: Cochlear EH was found in 25 of the 32 ears, and vestibular EH in 11. The rate of EH was significantly higher in symptomatic ears; however, the existence of EH was not related to SIR values. Nevertheless, SIR values in the basal turn were significantly higher 4 and 24 h after injection of gadolinium in patients aged ≥50 years. Conclusion and significance: Higher SIR values observed in older patients with EH indicate severe disturbances of the BPB in the cochlea, which may account for intractable inner ear disturbances in older patients.